ANALISIS EFEKTIFITAS MEDIA PEMBELAJARAN BERBASIS GAME EDUKASI DALAM PEMBEJARAN IPA DI SEKOLAH DASAR : A SYSTEMATIC LITERATUR REVIEW - Widianto, Dwi Nur; Rohmani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Educational game-based learning media is an innovation in education that raises the bar for science instruction in elementary schools by fusing entertaining and educational elements. This study aims to assess how educational game-based learning resources affect primary school students' scientific learning results. The method used is a Systematic Literature Review (SLR), and the data comes from Google Scholar. The literature search process involved several steps: the first stage produced 361,000 documents using the keyword